MANAGER'S BELIEFS ABOUT QUALITY IMPROVEMENT: AN INVESTIGATION ON THE MALAYSIAN ELECTRICAL AND ELECTRONICS INDUSTRY - Suhaiza Hanim Mohamad Zailani (Asian Academy of Management Journal, 2000)
As quality improvement is a highly controversial issue in the business community, it is interesting to see whether decisions about implementation are influenced by the managers' beliefs about the effect of quality improvement on the companies' market performance. This paper investigates managers' beliefs about quality improvement, which have promoted the growth of competitive advantage amongst Malaysian electrical and electronics companies that adopted the approaches to quality improvement of TQM or ISO 9000.